Protocol for covalent-targeted and activatable photoacoustic imaging agent for tumor imaging in mice - Jiho Song; Tianqu Zhai; Janggun Jo; Jae Won Chang (STAR Protocols)
Summary: Activatable photoacoustic imaging probes offer a strategy to efficiently reduce background noise from endogenous chromophores. We present a protocol for tumor imaging in mice using an activatable covalent photoacoustic imaging probe, NOx-JS013. We describe steps for synthesizing NOx-JS013, in vitro and in situ validation through gel-based activity-based protein profiling and cellular imaging, and tumor imaging of aggressive prostate cancer mouse models. This approach provides a strategy for mitigating background noise in the development of photoacoustic imaging probes.For complete details on the use and execution of this protocol, please refer to Song et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.